User Interface of Atmospheric Dispersion Simulations for Nuclear Emergency Countermeasures. (December 2017) - El-Asaad, Hamza; Nagai, Haruyasu; Sagara, Hiroshi
Abstract: In the event of a nuclear emergency, evacuation experts will have very limited time to make life saving decisions. Therefore, it is very important to provide these experts with knowledge of plume characteristics which are generated by an intuitive user interface; backed by simulations of radionuclide dispersions to better assist experts in evacuation planning. This study aims to verify the effectiveness of the user interface that can provide a one year meteorological and dispersion data based on WSPEEDI-II library. Such a user interface might be beneficial to risk and crisis management planning in case of a radioactive dispersion.